A biological timer in the fat body comprising Blimp-1, ?Ftz-f1 and Shade regulates pupation timing in Drosophila melanogaster. - Akagi, K.; Sarhan, M.; Sultan, A.R.; Nishida, H.; Koie, A.; Nakayama, T.; Ueda, H. (Development, 2016)
During the development of multicellular organisms, many events occur with precise timing. In Drosophila melanogaster, pupation occurs about 12?h after puparium formation and its timing is believed to be determined by the release of a steroid hormone, ecdysone (E), from the prothoracic gland. Here, we demonstrate that the ecdysone-20-monooxygenase Shade determines pupation timing by converting E to 20-hydroxyecdysone (20E) in the fat body, which is the organ that senses nutritional status. The timing of shade expression is determined by its transcriptional activator ?Ftz-f1. The ?ftz-f1 gene is activated after a decline in the expression of its transcriptional repressor Blimp-1, which is temporally expressed around puparium formation in response to a high titer of 20E. The expression level and stability of Blimp-1 is critical for the precise timing of pupation. Thus, we propose that Blimp-1 molecules function like sand in an hourglass in this precise developmental timer system. Furthermore, our data suggest that a biological advantage results from both the use of a transcriptional repressor for time determination and the association of developmental timing with nutritional status of the organism.